2012
DOI: 10.3402/fnr.v56i0.5728
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins and minerals: issues associated with too low and too high population intakes

Abstract: There is an ongoing increase in the availability of foods fortified with micronutrients and dietary supplements. This may result in differing intakes of micronutrients within the population and perhaps larger differences in intakes. Insight into population micronutrient intakes and evaluation of too low or too high intakes is required to see whether there are potential problems regarding inadequacy or excessive intakes. Too low population intakes are evaluated against an estimated average requirement; potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The investigated FS were multi-ingredient, contained various configurations of minerals and vitamins, and therefore differed in levels of essential elements. From the perspective of health protection, it is important to evaluate whether their concentrations do not exceed safety/guideline levels because an excessive intake can lead to various adverse effects including neurotoxic responses (Mn), cardiotoxicity (Co), gastrointestinal symptoms (Cu, Fe, K, Mg), altered immune function (Zn) or unwanted cardiovascular events (Ca) (Verkaik-Kloosterman et al 2012). Generally, our study demonstrated that the multi-ingredient FS produced in the EU have essential element concentrations decidedly below upper safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…The investigated FS were multi-ingredient, contained various configurations of minerals and vitamins, and therefore differed in levels of essential elements. From the perspective of health protection, it is important to evaluate whether their concentrations do not exceed safety/guideline levels because an excessive intake can lead to various adverse effects including neurotoxic responses (Mn), cardiotoxicity (Co), gastrointestinal symptoms (Cu, Fe, K, Mg), altered immune function (Zn) or unwanted cardiovascular events (Ca) (Verkaik-Kloosterman et al 2012). Generally, our study demonstrated that the multi-ingredient FS produced in the EU have essential element concentrations decidedly below upper safety limits.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty factor takes into account uncertainty including extrapolation from animals to humans, from sub-chronic to chronic exposure, and across age groups. Usual intakes at the UL therefore represent the highest level of intake that is likely to pose no risks of adverse effects in an age and gender group (18,19). As such, risks associated with intakes below the EAR and above the UL are different (18,19).…”
mentioning
confidence: 99%
“…Usual intakes at the UL therefore represent the highest level of intake that is likely to pose no risks of adverse effects in an age and gender group (18,19). As such, risks associated with intakes below the EAR and above the UL are different (18,19). The EAR is the midpoint of required intakes at which the risk of inadequacy is 50%, whereas close to the UL the risk is negligible as the UL is set an uncertainty factor lower than the intake levels at and above which adverse effects may be expected (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations